Mechanisms and Method. (July 2015) - Little, Daniel
Causal mechanisms theory (CMT) has provided an important contribution to the theory of social explanation. This article considers whether CMT also makes a contribution to improvement of social science methodology. Methodology serves as a guide to the construction of research questions and explanatory hypotheses. Research is guided by background assumptions about the ontology of the domain of investigation. CMT provides a valuable ontology for social science research. Furthermore, it provides a valuable research heuristic: "seek out the causal mechanisms that underlie an outcome of interest." CMT does indeed have valuable implications for social science investigation, hypothesis formation, and research strategy.